Participatory in Kampung’s Co-Housing Development: Learning From Kampung Muka, North Jakarta - Lutfiyah, Dinda; Herlily, Herlily (UI Scholars Hub, 2019)
Since its first appearance in Denmark in 1960s (Vestbro, 1992), co-housing communities responded basic needs for residents with a combination of fulfilment of individual privacy and the benefit of community life (McCamant, 1999). Kampung Muka as one of community indirectly has implemented some of co-housing principles according to local context. Participation in community life becomes in a form of participatory value which is one of the co-housing principles. Forth, this form of participatory is being learned on how its application and the impact of negotiating spaces in Kampung Muka. This writing aims to redefined co-housing concept according to the local context in Jakarta and expected to be able to suggest new understanding to the society about co-housing concept according to the local context.